Interventions for rosacea based on the phenotype approach: an updated systematic review including GRADE assessments3. (10th March 2019) - van Zuuren, E.J.; Fedorowicz, Z.; Tan, J.; van der Linden, M.M.D.; Arents, B.W.M.; Carter, B.; Charland, L.
Summary: Background: Rosacea is a common chronic facial dermatosis. Classification of rosacea has evolved from subtyping to phenotyping. Objectives: To update our systematic review on interventions for rosacea. Methods: We searched CENTRAL, MEDLINE, Embase, LILACS, Science Citation Index and ongoing trials registers (March 2018) for randomized controlled trials. Study selection, data extraction, risk‐of‐bias assessment and analyses were carried out independently by two authors. Grading of Recommendations, Assessment, Development and Evaluations (GRADE) was used to assess certainty of evidence. Results: We included 152 studies (46 were new), comprising 20 944 participants. Topical interventions included brimonidine, oxymetazoline, metronidazole, azelaic acid, ivermectin and other topical treatments. Systemic interventions included oral antibiotics, combinations with topical treatments or other systemic treatments. Several studies evaluated laser or light‐based treatment. We present the most current evidence for rosacea management based on a phenotype‐led approach. Conclusions: For reducing temporarily persistent erythema there was high‐certainty evidence for topical brimonidine and moderate certainty for topical oxymetazoline; for erythema and mainly telangiectasia there was low‐to‐moderate‐certainty evidence for laser and intense pulsed light therapy. For reducing papules/pustules there was high‐certainty evidence for topical azelaic acid and topical ivermectin; moderate‐to‐high‐certainty evidence for doxycycline 40 mg modified release (MR) and isotretinoin; and moderate‐certainty evidence for topical metronidazole, and topical minocycline and oral minocycline being equally effective as doxycycline 40 mg MR. There was low‐certainty evidence for tetracycline and low‐dose minocycline. For ocular rosacea, there was moderate‐certainty evidence that oral omega‐3 fatty acids were effective and low‐certainty evidence for ciclosporin ophthalmic emulsion and doxycycline. Abstract : What's already known about this topic? Rosacea is a chronic facial inflammatory dermatosis. The diagnosis and classification of rosacea have evolved from a subtype approach to a phenotype approach. Effective and safe interventions include brimonidine in temporarily reducing persistent erythema; laser‐ and light‐based therapies for mainly telangiectasia; topical azelaic acid, metronidazole and ivermectin, along with oral doxycycline and isotretinoin, for papules/pustules; and topical ciclosporin ophthalmic emulsion for ocular rosacea. What does this study add? A phenotype‐based approach with GRADE certainty‐of‐evidence assessments. Topical oxymetazoline reduces temporarily persistent erythema (moderate‐certainty evidence). There is moderate‐certainty evidence that topical minocycline is effective in treating papules/pustules, and oral minocycline is as effective as doxycycline 40 mg modified release. Low‐dose isotretinoin 0·25 mg kg −1 greatly reduces papules/pustules vs. placebo (high‐certainty evidence). Omega‐3 fatty acids improve symptoms of dry eyes and tear gland function (moderate‐certainty evidence). Linked Comment:  Le Cleach and Cribier. Br J Dermatol 2019;181 :11–12 . Plain language summary available online